Gastroesophageal reflux disease and tooth erosion: SEPAHAN systematic review no. 10 - Malih Sadat Firouzei; Saber Khazaei; Parastoo Afghari; Afghari Savabi; Omid Savabi; Ammar Hassanzadeh Keshteli; Peyman Adibi (Wolters Kluwer Medknow Publications, 2011)
Many systemic diseases affect oral health. The aim of this research was to conduct a systematic review on the association between dental erosion (DE) and gastroesophageal reflux disease (GERD) and the effect of saliva's flow rate, buffering capacity and oral microbial changes caused by GERD. All descriptive, analytical studies up to December 2011 that have relevant objectives, proper sampling method and sufficient results were included by searching PubMed and Scopus electronic data bases. Fifteen studies were selected according to our inclusion criteria (10 in adult and 5 in children population). There was a strong association between DE and GERD in the adult population, and the relationship in the children population was found to be of less importance. Early diagnosis and treatment of refluxed acid in both age groups through lifestyle changes and medications can prevent further damage and tooth loss.